2011
DOI: 10.1590/s0104-66322011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrogen removal over nitritation/denitritation using phenol as carbon source

Abstract: -A laboratory scale activated sludge sequencing batch reactor was operated in order to obtain total removal of influent ammonia (200; 300 and 500 mg NH 3 -N.L -1 ) with sustained nitrite accumulation at the end of the aerobic stages with phenol (1,000 mg C 6 H 5 OH.L -1 ) as the carbon source for denitrifying microorganisms during the anoxic stages. Ammonia removal above 95% and ratios of (NO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
0
9
0
1
Order By: Relevance
“…Fux et al (2006) obtained slightly lower efficiencies of TN removal (85-90 %) in a similar system fed with ethanol as the organic carbon source. Queiroz et al (2011) used phenol as an external carbon source for treating synthetic sludge digester liquors in the process nitritation/denitritation. The removal efficiencies of ammonium nitrogen (NH 4 -N) varied in the range of 89-99 %.…”
Section: Kinetics Of Denitrification During the Acclimation Experimentsmentioning
confidence: 99%
“…Fux et al (2006) obtained slightly lower efficiencies of TN removal (85-90 %) in a similar system fed with ethanol as the organic carbon source. Queiroz et al (2011) used phenol as an external carbon source for treating synthetic sludge digester liquors in the process nitritation/denitritation. The removal efficiencies of ammonium nitrogen (NH 4 -N) varied in the range of 89-99 %.…”
Section: Kinetics Of Denitrification During the Acclimation Experimentsmentioning
confidence: 99%
“…In a similar research, aiming at nitrification via nitrite, QUEIROZ et al (2011) worked with an initial free ammonia concentration of approximately 12 mg L −1 , an internal reactor temperature of 35 °C and an initial concentration of ammoniacal nitrogen varying between 200 and 500 mg L −1 . The authors observed that such free ammonia concentration was insufficient to inhibit nitrification, even though within the parameters recommended by the literature.…”
Section: Phase IIImentioning
confidence: 99%
“…De uma forma geral, a matéria orgânica degradável vai decrescendo em concentração de acordo com a idade do aterro, prevalecendo compostos inertes recalcitrantes, reduzindo desta maneira a razão DBO/DQO (demanda bioquímica de oxigênio/demanda química de oxigênio); sendo por vezes necessária a adição de uma fonte externa de carbono para que o processo de desnitrificação seja realizado completamente (BUTKOVSKYI, 2009;FREITAS, 2009 Ultimamente, tem havido interesse crescente na nitrificação e desnitrificação via nitrito, pois de acordo com o balanço estequiométrico o fornecimento de oxigênio dissolvido para as bactérias autotróficas converterem amônia a nitrito é menor, assim como a quantidade de matéria orgânica doadora de elétrons para a desnitrificação (QUEIROZ et al 2011;ZAFARZADEH et al, 2011). A desnitrificação via nitrito requer um consumo 25% menor de oxigênio dissolvido para a oxidação do nitrogênio amoniacal e 40% menor de fonte de carbono para a desnitrificação do nitrito gerado (SPAGNI; MARSILI-LIBELLI; LAVAGNOLO, 2008 (VON SPERLING, 1997).…”
Section: No Tratamento Biológico O Nitrogênio Amoniacal é Transformadounclassified